The association between dietary polyphenol intake and the odds of metabolic syndrome - Maede Makhtoomi; Zainab Shateri; Ava Mashoufi; Mehran Nouri; Behnam Honarvar; Parisa Keshani (Scientific Reports, 2024)
Abstract Oxidative stress plays a role in the pathophysiology of metabolic syndrome (MetS), and one of the most important features of polyphenols is their antioxidant properties. However, there is no universal consensus on the effectiveness of polyphenols in treating Mets. Therefore, the present study aimed to investigate the association between polyphenols and MetS in an Iranian sample. This cross-sectional study was conducted on an adult population sample from Shiraz, in southern Iran. MetS was calculated using the criteria of the Adult Treatment Panel III (ATP III), which defines MetS as the presence of three or more of the specified risk factors. A validated food frequency questionnaire (FFQ) was used to measure the participant’s food intake. The association between polyphenol intake and the odds on MetS and its components was assessed using logistic regression. In both univariate and multivariate models, the association between polyphenol intake and the risk of MetS was not significant. However, after adjusting for potential confounders in the multivariate model, each unit change in flavonol, flavanone and isoflavones intake was associated with a lower, higher, and higher odds of MetS, respectively (flavonols: odds ratio (OR) = 0.926, 95% confidence interval (CI) 0.891–0.963, P < 0.001—flavanones: OR = 1.007, 95% CI: 1.001–1.014, P = 0.034—isoflavones: OR = 4.920, 95% CI: 1.057–22.894, P = 0.042). Additionally, no significant association was found between polyphenol intake and the risk of MetS components. However, in the multivariate model, after adjusting for potential confounders, a significant association was observed between polyphenol intake and lower odds of high waist circumference (OR = 0.998, 95% CI: 0.996–0.999, P = 0.032). The present study did not reveal a significant association between overall polyphenol intake and the odds of MetS. However, certain subclasses of polyphenols appear to be associated with the likelihood of MetS and its components.